The effect of being imitated on empathy for pain in adults with high-functioning autism: Disturbed self–other distinction leads to altered empathic responding. (August 2018) - De Coster, Lize; Wiersema, Jan R; Deschrijver, Eliane; Brass, Marcel
Autism spectrum disorder is a neurodevelopmental disorder that is associated with problems in empathy. Recent research suggests that impaired control over self–other overlap based on motor representations in individuals with autism spectrum disorder might underlie these difficulties. In order to investigate the relationship of self–other distinction and empathy for pain in high-functioning autism and matched controls, we manipulated self–other distinction by using a paradigm in which participants are either imitated or not by a hand on a computer screen. A strong pain stimulus is then inflicted on the observed hand. Behavioral and physiological results in this study showed that overall affective responses while watching pain movies were the same in adults with high-functioning autism as in controls. Furthermore, controls showed higher affective responding after being imitated during the whole experiment, replicating previous studies. Adults with high-functioning autism, however, showed increased empathic responses over time after being imitated. Further exploratory analyses suggested that while affective responding was initially lower after being imitated compared to not being imitated, affective responding in the latter part of the experiment was higher after being imitated. These results shed new light on empathic abilities in high-functioning autism and on the role of control over self–other representational sharing.